1999
DOI: 10.1002/(sici)1098-240x(199904)22:2<95::aid-nur2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Acute confusion indicators: Risk factors and prevalence using MDS data

Abstract: Long-term care (LTC) Minimum Data Set (MDS) data from a Midwestern state were analyzed to validate whether components of a conceptual model developed from findings in acute care identified acute confusion risk variables in LTC. The prevalence of probable acute confusion in this sample was 13.98% (n = 324). Using a cross-sectional design, both univariate and unconditional stepwise logistic regression analyses were accomplished with presence or absence of probable acute confusion as the outcome variable (N = 2,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Mitchell et al found that approximately 2% of nursing home residents die from advanced dementia and cancer. 19 The MDS is carried out quarterly, and with a change in resident status and is completed by multiple providers 39,40 who are responsible for charting diagnoses and medication administration. An assumption is that the data were coded and entered correctly in the nursing home databases, MDS records and the medication administration records.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al found that approximately 2% of nursing home residents die from advanced dementia and cancer. 19 The MDS is carried out quarterly, and with a change in resident status and is completed by multiple providers 39,40 who are responsible for charting diagnoses and medication administration. An assumption is that the data were coded and entered correctly in the nursing home databases, MDS records and the medication administration records.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium was associated with rejection of care in the analysis. Although delirium has been reported to be common in NHs, [44][45][46] its recognition remains challenging. 47 The Confusion Assessment Method, a sensitive measure to detect delirium, was used.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire asked respondents to rank these activities from highest priority (1) to lowest priority (7). The rank-order portion presented (in alphabetical order) the following practice activities, which the literature identifies as being common among gerontology practitioners and as affecting recovery from illness: cognitive assessment, including screening for delirium, depression, acute confusion, and dementia (Inouye, 1998;Mentes, Culp, Maas, & Rantz, 1999;Rockwood, 1993;Zal, 1999); discharge planning (Berkman, 1995;Nicholias & Leuner, 1991); discussion of advance directives (Basile, 1998;Gamble, McDonald, & Lichstein, 1991;Tierney et al, 2001); assessment of functional status (Inouye et al, 1993); pain management (Loeb, 1999); assessment of need for physical or occupational therapy (Corcoran, 1991;Narain et al, 1998); and wound/skin assessment (Brandeis, Berlowitz, Hossain, & Morris, 1995;Young, 1989). Demographic items asked for discipline classification and specialty only.…”
Section: Instrumentsmentioning
confidence: 99%